A Case of Hypermucoviscosity Phenotype of Klebsiella pneumoniae Liver Abscess Saved by Damage Control Strategy. (29th September 2022) - Sato, Keita; Takahashi, Koji; Kusuta, Tsukasa
Abstract : Liver abscess caused by the Hypermucoviscosity phenotype of Klebsiella pneumoniae (HKp) is characterized by high tissue invasiveness and multiple systemic infections. This leads to sepsis, multiple organ failure, and coagulopathy. An 80 year old man came to our hospital with a complaint of malaise and went into hemorrhagic shock after percutaneous transhepatic drainage of a liver abscess caused by HKp. An emergency laparotomy was performed, but the patient suffered from severe coagulopathy and underwent damage control surgery. HKp liver abscesses must be operated on in the presence of multiple organ failure and disseminated intravascular coagulation (DIC) complications when medical treatment is refractory. In these situations, a two-stage damage control strategy should be considered: hemostasis and infection control at the initial surgery and hepatic resection.